Mitochondrion-mediated cell death: dissecting yeast apoptosis for a better understanding of neurodegeneration - Braun, Ralf J. (Frontiers in Oncology, 2012)
Mitochondrial damage and dysfunction are common hallmarks for neurodegenerative disorders, including Alzheimer, Parkinson, Huntington diseases, and the motor neuron disorder amyotrophic lateral sclerosis. Damaged mitochondria pivotally contribute to neurotoxicity and neuronal cell death in these disorders, e.g., due to their inability to provide the high energy requirements for neurons, their generation of reactive oxygen species, and their induction of mitochondrion-mediated cell death pathways. Therefore, in-depth analyses of the underlying molecular pathways, including cellular mechanisms controlling the maintenance of mitochondrial function, is a prerequisite for a better understanding of neurodegenerative disorders. The yeast Saccharomyces cerevisiae is an established model for deciphering mitochondrial quality control mechanisms and the distinct mitochondrial roles during apoptosis and programmed cell death. Cell death upon expression of various human neurotoxic proteins has been characterized in yeast, revealing neurotoxic protein-specific differences. This review summarizes how mitochondria are affected in these neurotoxic yeast models, and how they are involved in the execution and prevention of cell death. I will discuss to which extent this mimics the situation in other neurotoxic model systems, and how this may contribute to a better understanding of the mitochondrial roles in the human disorders.